Health Outcomes Associated With Internalizing Problems in Early Childhood and Adolescence - Jamnik, Matthew R.; DiLalla, Lisabeth F. (Frontiers in Psychology, 2019)
Physical and mental health problems are becoming more common among the general population. Studies examining mental and physical health often indicate that mental illness early in life is associated with more detrimental health outcomes later. However, additional work is needed to better identity which psychological problems may contribute to poorer health outcomes. Given recent increases in childhood anxiety and depression specifically, it is beneficial to further investigate the relationship between internalizing problems, both early and later in life, and related health problems. Furthermore, little work has focused on studying internalizing problems in children as young as preschool-aged. Therefore, the current project used a longitudinal design to assess the effects of preschool and adolescent internalizing problems on health-related problems in adolescence. We analyzed data from 70 youth (47% male) who had been tested in our lab when they were 5 years old and then were administered questionnaires over a telephone interview when they were adolescents, between the ages of 12 and 20 years old. We used multi-informant measures, including parent-report at age 5 and youth-report at follow-up, 7 to 15 years later. Parents reported on children’s internalizing behavior problems and negative emotionality. Youth reported on their own internalizing behavior problems as well as health problems, physical activity, and overeating behaviors. Path modeling was used to examine predictions of internalizing and health behaviors. At age 5, parent-reported negative emotionality and internalizing problems were related, in addition to 5-year-old internalizing predicting health problems and overeating at follow-up. At follow-up, youth-reported internalizing was positively related to health problems and negatively related to physical activity, suggesting some similarities and differences between parent and youth responses. Additionally, girls reported significantly higher rates of internalizing and health problems at follow-up. These results indicate a significant relationship between preschool-aged and adolescent internalizing problems and related health outcomes experienced in adolescence.